Solid bone tumors of the spine: Diagnostic performance of apparent diffusion coefficient measured using diffusion‐weighted MRI using histology as a reference standard. Issue 4 (29th July 2017) - Pozzi, Grazia; Albano, Domenico; Messina, Carmelo; Angileri, Salvatore Alessio; Al‐Mnayyis, Asma'a; Galbusera, Fabio; Luzzati, Alessandro; Perrucchini, Giuseppe; Scotto, Gennaro; Parafioriti, Antonina; Zerbi, Alberto; Sconfienza, Luca Maria
Abstract : Purpose: To assess the diagnostic performance of mean apparent diffusion coefficient (mADC) in differentiating benign from malignant bone spine tumors, using histology as a reference standard. Conventional magnetic resonance imaging (MRI) sequences have good reliability in evaluating spinal bone tumors, although some features of benign and malignant cancers may overlap, making the differential diagnosis challenging. Materials and Methods: In all, 116 patients (62 males, 54 females; mean age 59.5 ± 14.1) with biopsy‐proven spinal bone tumors were studied. Field strength/sequences: 1.5T MR system; T1 ‐weighted turbo spin‐echo (repetition time / echo time [TR/TE], 500/13 msec; number of excitations [NEX], 2; slice thickness, 4 mm), T2 ‐weighted turbo spin‐echo (TR/TE, 4100/102 msec; NEX, 2; slice thickness, 4 mm), short tau inversion recovery (TR/TE, 4800/89 msec; NEX, 2; slice thickness, 4 mm, IT, 140 msec), axial spin‐echo echo‐planar diffusion‐weighted imaging (DWI) (TR/TE 5200/72 msec; slice thickness 5 mm; field of view, 300; interslice gap, 1.5 mm; NEX, 6; echo‐planar imaging factor, 96; no parallel imaging) with b‐values of 0 and 1000 s/mm², and 3D fat‐suppressed T1 ‐weighted gradient‐recalled‐echo (TR/TE, 500/13 msec; slice thickness, 4 mm) after administration of 0.2 ml/kg body weight gadolinum‐diethylenetriamine pentaacetic acid. Two readers manually drew regions of interest on the solid portion of the lesion (hyperintense on T2 ‐weighted images, hypointense on T1 ‐weighted images, and enhanced after gadolinium administration on fat‐suppressed T1 ‐weighted images) to calculate mADC. Histology was used as the reference standard. Tumors were classified into malignant primary tumors (MPT), bone metastases (BM), or benign primary tumors (BPT). Statistical tests: Nonnormality of distribution was tested with the Shapiro–Wilk test. The Kruskal–Wallis and Mann–Whitney U ‐test with Bonferroni correction were used. Sensitivity and specificity of the mADC values for BM, MPT, and BPT were calculated. Approximate receiver operating characteristic curves were created. Interobserver reproducibility was evaluated using the intraclass correlation coefficient (ICC). Results: The mADC values of MPT ( n  = 35), BM ( n  = 65), and BPT ( n  = 16) were 1.00 ± 0.32 (0.59–2.10) × 10 −3 mm 2 /s, 1.02 ± 0.25 (0.73–1.96) × 10 −3 mm 2 /s, 1.31 ± 0.36 (0.83–2.14) × 10 −3 mm 2 /s, respectively. The mADC was significantly different between BPT and all malignant lesions (BM+MPT) ( P < 0.001), BM and BPT ( P  = 0.008), and MPT and BPT ( P  = 0.008). No difference was found between BM and MPT ( P  = 0.999). An mADC threshold of 0.952 × 10 −3 mm 2 /s yielded 81.3% sensitivity, 55.0% specificity. Accuracy was 76% (95% confidence interval [CI] = 63.9%–88.1%). Interobserver reproducibility was almost perfect (ICC = 0.916; 95% CI = 0.879–0.942). Conclusion: DWI with mADC quantification is a reproducible tool to differentiate benign from malignant solid tumors with 76% accuracy. The mADC values of BPT were statistically higher than that of malignant tumors. However, the large overlap between cases may make mADC not helpful in a specific patient. Level of Evidence: 3 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2018;47:1034–1042.